Quasi-projective synchronization of memristor-based complex valued recurrent neural network with time-varying delay and mismatched parameters - Kumar A.; Das S.; Joo Y.H. (My University, 2025)
This article focuses on the quasi-projective synchronization for a class of non-identical memristor-based complex-valued recurrent neural networks (MCVRNNs) with time-varying delays and parameters’ mismatched. Here, the quasi-projective synchronization is presented in two ways based on the Halanay inequality and some useful techniques. Some novel sufficient conditions are firstly derived for quasi-projective synchronization criteria of non-identical memristor-based CVRNNs with time-varying delays and parameters’ mismatched by using the matrix measure method. And then, by using the Lyapunov-Krasovskii functional, another sufficient stabilization condition for quasi-projective synchronization of the concerned model is presented. Finally, two numerical simulation results are given to demonstrate the usefulness and persistence of the proposed methods under some conditions. © 2023 Elsevier B.V.